Exploring Student’s Anxiety in Learning Performance Through Pair Work Activity - Azkarina, Shinta; Machfudi, Moch. Imam (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
Anxiety in the learning process is one of the significant obstacles experienced by many students and can affect their academic performance. This study aims to explore how pair work activities can help reduce student learning anxiety at MAN 2 Probolinggo. This study uses a qualitative approach with a case study design. Data collection techniques were conducted through in depth interviews, direct classroom observations, and documentation. The results of the study indicate that pair work activities have a positive impact on reducing learning anxiety. Students feel more confident, comfortable, and active when learning with supportive partners. Interactions in pair work create a safe and collaborative learning environment, encouraging students to be more open and less afraid of making mistakes. Although challenges such as mismatched pairs or dominance by certain students exist, this strategy is generally proven effective. Therefore, paired work can be adopted as a routine learning strategy that supports the creation of an inclusive and participatory learning process, particularly for students with high levels of anxiety.